Allelopathy and weed control ability of three cover crops residues, in conservation of agriculture (Bangladesh Journal of Botany, 2023)
The weed suppressive potential of three cover crops: two forage hybrids of corn and sorghum and a local population of millet, used in conservation of agriculture was investigated. The allelopathic potential of cover crops was studied based on bio-assays. The effect of three tested crops were used on weed dynamics (weed density, Weed Control Efficiency (WCE). Two types of residues management (TRM) were followed: standing and incorporated residues (SR, IR).Forage residues showed an allelopathic effect on germination and seedlings growth of rye-grass. Sorghum significantly reduced weed density. Incorporated residues method was more effective than standing residues in reducing weed density. Millet  residues was more efficient to control weeds whereas corn residues increased weed biomass. Weed Control Efficiency was also influenced by two types of residues management which showed a highly significant interaction with tested crops.Bangladesh J. Bot. 52(3): 845-852, 2023 (September)